Exploring student perspectives of Expert by Experience involvement in Clinical Psychology training using a story completion method : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Manawatū, Aotearoa New Zealand. EMBARGOED until 2 September 2026 - Zimmerman, Hannah (Massey University, 2026)
The Lancet Commission have identified the urgent need to eradicate mental health stigma and discrimination. A key recommendation to support this is mandating teaching on the needs and rights of people with mental health conditions, co-delivered by people with lived experience, in health and social professional and vocational training courses. However, the involvement of people with lived/living experience of mental distress, or ‘experts by experience’ (EBE), in clinical psychology training in Aotearoa is minimal. Barriers to increasing effective EBE involvement may be found in student attitudes. The aim of my research was to explore student perspectives of EBE involvement in clinical psychology training. Using a story completion method, I explored the assumptions, ideas, and language that participants engaged with when writing about EBE involvement, to help elucidate social understandings that underlie student perspectives. The stories produced by participants contained several tensions. Firstly, participants contrasted the humanity provided by EBE involvement with the dominance of a biomedical approach in training that views mental distress in less than human ways. Secondly, EBE expertise was valued, but was also devalued if it challenged the superiority of psychology, or the expert role of students and psychologists. Thirdly, students were depicted as relating to and connecting to EBE experience, but also as unable to understand and as othering of EBE. These findings highlight the need for a shift in how mental distress is viewed, and the way knowledge is produced and valued within psychology. Such a shift requires changes at the teaching, organisational, and wider disciplinary level, including through supporting EBE in leadership roles, and making changes to organisational policy, accreditation standards, training requirements, and professional competencies. Such change would support the meaningful involvement of EBE in clinical psychology training, and the eradication of mental health stigma and discrimination in higher education.
Embargoed until 2 September 2026
Keywords: Clinical psychologists; Training of; Competency-based education; Experiential learning; New Zealand; Narrative inquiry (Research method); Distress (Psychology); 520302 Clinical psychology